Antigenic Imprinting Dominates Humoral Responses to New Variants of SARS-CoV-2 in a Hamster Model of COVID-19 - Joran Degryse; Elke Maas; Ria Lassaunière; Katrien Geerts; Yana Kumpanenko; Birgit Weynand; Piet Maes; Johan Neyts; Hendrik Jan Thibaut; Yeranddy A. Alpizar; Kai Dallmeier (Microorganisms)
The emergence of SARS-CoV-2 variants escaping immunity challenges the efficacy of current vaccines. Here, we investigated humoral recall responses and vaccine-mediated protection in Syrian hamsters immunized with the third-generation Comirnaty® Omicron XBB.1.5-adapted COVID-19 mRNA vaccine, followed by infection with either antigenically closely (EG.5.1) or distantly related (JN.1) Omicron subvariants. Vaccination with the YF17D vector encoding a modified Gamma spike (YF-S0*) served as a control for SARS-CoV-2 immunity restricted to pre-Omicron variants. Our results show that both Comirnaty® XBB.1.5 and YF-S0* induce robust, however, poorly cross-reactive, neutralizing antibody (nAb) responses. In either case, total antibody and nAb levels increased following infection. Intriguingly, the specificity of these boosted nAbs did not match the respective challenge virus, but was skewed towards the primary antigen used for immunization, suggesting a marked impact of antigenic imprinting, confirmed by antigenic cartography. Furthermore, limited cross-reactivity and rapid decline in nAbs induced by Comirnaty® XBB.1.5 with EG.5.1 and, more concerning, JN.1, raises doubts about sustained vaccine efficacy against recent circulating Omicron subvariants. In conclusion, we demonstrate that antigenic imprinting plays a dominant role in shaping humoral immunity against emerging SARS-CoV-2 variants. Future vaccine design may have to address two major issues: (i) overcoming original antigenic sin that limits the breadth of a protective response towards emerging variants, and (ii) achieving sustained immunity that lasts for at least one season.